KARAKTERISTIK BERPIKIR GEOMETRI SISWA PADA TINGKAT VISULISASI, ANALISIS, DAN DEDUKSI INFORMAL BERDASARKAN TEORI VAN HIELE - Khumayroh, Alfatikha Anik; Yudianto, Erfan; Setiawan, Toto' Bara; Susanto, Susanto; Pambudi, Didik Sugeng (Department of Mathematics Education , University of Jember, 2019)
Geometry is one of the material in mathematics that is studied by students. In measuring students' geometry abilities, one of the efforts can use van Hiele's theory. This research is a descriptive study with the subject of the research is grade IX D students of SMP Negeri 2 Jember. The purpose of this study is to describe the characteristics ofthinking geometry students'at the level of visualization, analysis, and informal deduction. Research subjects were 5 students with 2 students at the visualization level, 2 students at the analysis level, and 1 student at the level informal deduction. The results of this study indicate that (1) Visualization subjects can identify, classify, compare and determine the types ofshapes quadrilateralbased on their visual appearance and can draw with labeling simple. (2) The subject of analysis can identify, analyze, classify, define and compare quadrilateral shapes according to the relationship between their properties. (3) The subject of informal deduction can define and compareshapes quadrilateralby looking at the relationship between quadrilateral shapes